Occurrence and Phylogenetic Analysis of DWV in Stingless Bee (Apidae sp.) in China: A Case Report - Zhang, Lina; Deng, Yanchun; Zhao, Hongxia; Zhang, Ming; Hou, Chunsheng (Frontiers in Insect Science, 2021)
Honey bees play a vital role in providing pollination service for agricultural crops and wild flowering plants. However, the spillover risk of their pathogens to other pollinators or wild insects are receiveing the concerns. There were a few evidences that stingless bees can carry honey bee viruses but little is known about the presence of honey bee viruses in stingless bee in China. Here, we investigated the occurrence of the main honey bee pathogens including bacterial, fungi and virus in the stingless bees (Apidae：sp.). Our results showed that the stingless bees (Apidae: sp.) were mainly infected with DWV-A but no DWV-B and DWV-C. Phylogentic analysis on the fragment of lp, RdRp and VP3 of DWV-A indicated that genetic variation in VP3 might an important indicator for host-specific viruses but it had to further study. Our results indicated that DWV-A is not only the major strain of virus currently circulating in managed bee colony in China and globally but in stingless bee species.